Study on maternal and foetal outcome of pregnancy with positive glucose tolerance test by diabetes in pregnancy study group diagnostic criteria - Lakshmi Satyavathi, G. Anantha; A., Chitti Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Diabetes in Pregnancy Study group, India (DIPSI) diagnostic criteria is a single step method of screening and diagnosis of gestational Diabetes. Therefore, this prospective study was undertaken to ascertain the validity of DIPSI criteria to diagnose GDM based on pregnancy outcome in Indian population. Method: The present Hospital based prospective study was conducted at OBGY department, GSL Medical College and General Hospital, Rajahmundry during 2013 to 2015. Women who were attending OBGY OPD for Antenatal check-ups within 24-28 weeks of GA during the study period were included in the study. Each mother at 24-28 weeks of gestation irrespective of last meal timing, fasting / non fasting was given 75 gm glucose dissolved in a glass of 200 ml water to drink and after two hours venous blood was collected. Result: Out of 500 cases, 26 cases are diagnosed as having gestational diabetes by DIPSI criteria and 474 cases are Normal glucose tolerant. Maximum number 53.9% of cases diagnosed as GDM by DIPSI are of age >25 yrs (53.9%), primigravida (65.7%), BMI>25 (57.7%). In present study, family h/o diabetes is a risk factor for GDM Conclusion: Our results suggest that a policy of universal screening for GDM should be adopted in all antenatal clinics and 75 gm OGTT has a high predictive value. This single step procedure is a simple economic and feasible method. It serves both for the purpose of screening and diagnosis at the same time.